Analisis Perubahan Nama Gereja Dayak Evangelis Menjadi Gereja Kalimantan Evangelis: Studi Histografi - Saputra, Hadi (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
So far, the history of the Kalimantan Evangelical Church (GKE) has always been associated with the efforts of the Dayak Evangelical Church (GDE) to become GKE, only looking at it from an ecumenical perspective, despite the fact that there is something very important, namely the removal of the Colonial roots behind the embedded Dayak word. In the struggle for independence that existed at that time, the word "GDE" was identified with the role of the Dayak people, who were considered to be supporting the Dutch colonial government. Historical research is classified in the "Historical Method,", which is a research method specifically used in historical research that passes through certain stages. Heuristics, data collection, and (historical) criticism, namely investigating whether historical traces are genuine both in form and content, Interpretation, and history. Historiography or presentation, namely presenting the synthesis obtained in the form of a narrative, The removal of the name Dayak was an attempt by the church to wash from the burden of past history, which identified Dayak and Colonial power. The church also tried to transform so that the ideals of the church's struggle were no longer just tribal interests but also those of a nationalist church.